COM651: Mass media and society / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (2016)
This course exposes students to the usage and effects of mass media, and how or why it has become an integral part of human life. Therefore to understand the system of mass communication would mean delving into the nature of the social, political and economic order. Studying the relationships of media and society, power structure, social culture and the social order is essential.